Contemporary Complex Systems and Their Dependability Proceedings of the Thirteenth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2-6, 2018, Brunów, Poland - Zamojski, Wojciech; Mazurkiewicz, Jacek; Sugier, Jarosław; Walkowiak, Tomasz; Kacprzyk, Janusz (Advances in Intelligent Systems and Computing, 2019)
This book presents the proceedings of the Thirteenth International Conference on Dependability and Complex Systems (DepCoS-RELCOMEX), which took place in the Brunów Palace in Poland from 2nd to 6th July 2018. The conference has been organized at the Faculty of Electronics, Wrocław University of Science and Technology since 2006, and it continues the tradition of two other events: RELCOMEX (1977-89) and Microcomputer School (1985-95). The selection of papers in these proceedings illustrates the broad variety of topics that are investigated in dependability analyses of today's complex systems. Dependability came naturally as a contemporary answer to new challenges in the reliability evaluation of these systems. Such systems cannot be considered only as structures (however complex and distributed) built on the basis of technical resources (hardware): their analysis must take into account a unique blend of interacting people (their needs and behaviours), networks (together with mobile properties, cloud-based systems) and a large number of users dispersed geographically and producing an unimaginable number of applications (working online). A growing number of research methods apply the latest advances in artificial intelligence (AI) and computational intelligence (CI). Today's complex systems are really complex and are applied in numerous different fields of contemporary life.